2021
DOI: 10.3390/ph14070611
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Events Potentially Associated to Remdesivir: An Analysis from the European Spontaneous Adverse Event Reporting System

Abstract: Remdesivir was recommended for hospitalized patients with COVID-19. As already reported in the Summary of Product Characteristics, most of remdesivir’s safety concerns are hepatoxicity and nephrotoxicity related. However, some cases have raised concerns regarding the potential cardiac events associated with remdesivir; therefore, the Pharmacovigilance Risk Assessment Committee of the European Medicines Agency requested to investigate all available data. Therefore, we analyzed all Individual Case Safety Reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 34 publications
(39 reference statements)
3
21
0
1
Order By: Relevance
“…The 94.31% of ICSRs were reported by HCPs in accordance with other studies [ 27 , 28 , 29 , 30 , 31 ]. In most ICSRs was reported one suspected drug and no concomitant drugs.…”
Section: Discussionsupporting
confidence: 90%
“…The 94.31% of ICSRs were reported by HCPs in accordance with other studies [ 27 , 28 , 29 , 30 , 31 ]. In most ICSRs was reported one suspected drug and no concomitant drugs.…”
Section: Discussionsupporting
confidence: 90%
“…Wang et al showed that the use of remdesivir therapy was related to hyponatremia and hypokalemia which was the leading cause of discontinuing remdesivir in some patients [ 53 ]. In addition, as in our study, Rafaniello et al showed that remdesivir was associated with a two-fold increased risk in cardiac adverse reactions compared to both hydroxychloroquine and azithromycin [ 54 ]. Again, the elevated number of mechanically ventilated patients in the TCZ-RMV group, compared to the TCZ-HCQ group, might contribute to the detection of myocarditis either due to mechanical ventilation or the use of RMV.…”
Section: Discussionsupporting
confidence: 79%
“…Data analysis revealed a twofold increased risk of an adverse cardiac event associated with remdesivir in comparison with hydroxychloroquine and azithromycin. The result of this study showed that remdesivir might increase the risk of adverse cardiac events [ 15 ]. Sanchez-Codez et al reported a 13-year-old boy with a history of bronchial asthma who was admitted with severe bilateral pneumonia and hypoxemia by COVID-19 with a baseline heart rate of 80–90 bpm.…”
Section: Literature Review On Cardiac Side Effectsmentioning
confidence: 99%